Method of partial averaging in the systems of standard form with discontinuous right-hand sides - Zverkova, T. S.; Plotnikov, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The scheme of partial averaging for systems of standard form with discontinuous right-hand sides is presented. The solutions are justified and estimated without assuming periodicity of the right-hand sides of the systems.